(3GdGYJUGe (B/s - (3GdTGWHj, EHQGgje Hf ehSi Hf eMeOs (3Jhaj (B790 (3gLQjs; (3GdgdGdj, Sdje Hf YjO Hf eMeOs 1957- ((3GdNHQ (B- (3GdSYhOjI (B:s (3OGQ GHf YaGf ,s, 1995)
(3jJfGhd GdcJGH GdHOY hJYQjagG hBKQgG Ydi GdOjf GdESdGej hGdCeI GdESdGejI(B.s
Keywords: (3GdHOY aj GdESdGes -- (3GdcHGFQs; (3GdHOYs